Valuing productivity costs using the friction‐cost approach: Estimating friction‐period estimates by occupational classifications for the UK. (27th April 2017) - Kigozi, Jesse; Jowett, Sue; Lewis, Martyn; Barton, Pelham; Coast, Joanna
Abstract: The friction cost approach has been proposed as an alternative to the human capital approach in estimating productivity costs. However, it is difficult, in practice, to apply this approach due to limited availability of context‐specific data. Using national and firm‐level data on vacancy durations sourced from 4 organisations, we estimated vacancy durations, and consequently, length of friction period for the United Kingdom disaggregated by occupational classification. We found comparable estimates to previously reported friction periods elsewhere. The disaggregated friction period analysis confirmed occupational class has an effect on the estimated length of the friction period. The research presents estimates on vacancy durations and friction periods necessary to use the friction cost approach in a practical way in economic evaluations.